The Influence of Work Environment and Work Discipline on Employee Performance through Job Satisfaction - Putra, Riyan Sisiawan; Agustina, Tri Siwi; Aziz, Azmin Azliza Binti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee performance is critical to organizational success, influenced by factors such as work environment, work discipline, and job satisfaction, yet their interplay in small manufacturing firms remains underexplored. This study aims to examine how the work environment and work discipline affect employee performance through job satisfaction at Barokah Jaya, a rubber processing company in Mojokerto, East Java. A quantitative approach was employed, involving all 52 employees as the sample, with data collected via questionnaires using a 1–5 Likert scale and analyzed using Partial Least Squares. Findings indicate that a supportive work environment, including adequate facilities and positive relationships, and strong work discipline, marked by adherence to regulations, significantly enhances employee performance. Work discipline also increases job satisfaction, which directly boosts performance and mediates the relationship between discipline and performance, but the work environment does not significantly affect satisfaction due to fair rewards and leadership. In conclusion, fostering a conducive work environment and enforcing discipline are essential for improving performance, with job satisfaction playing a key mediating role for discipline. These insights suggest that small firms should prioritize workplace improvements and disciplined practices to optimize employee outcomes.